An exploration of the relationship between financial inclusion and the wellbeing of youth in South Africa - Wilson, Shamilla (Graduate School of Business (GSB), 2022)
In South Africa, where 55.2 percent of youth are without a job, financial inclusion has been put forward as a way to tackle unemployment and the grinding poverty and inequality that come with it. The salient features of the discourses on financial inclusion tend to focus on increasing the accessibility and usability of financial services and products for those who are un- and/or under-banked, due to its promises of economic empowerment. Whilst there is an acknowledgement that a youth specific focus is needed there is a lack of scholarship on this demographic. Interventions for youth have tended to focus on banking youth early in life as well as increase their financial literacy and savings behaviour. The literature affirms that the objectives of youth specific financial inclusion efforts are meant to assist them in achieving their aspirations, and enable them to participate more fully within society. However, the heterogeneity of youth and the complexity of social and economic realities challenge assumptions that financial literacy and improved savings behaviour could support the multitude of youth in South Africa, especially as their realities manifest at the systemic rather than the individual level. This research study, therefore, set out to explore the relationship that youth have to the formal financial system and their wellbeing. The study employed qualitative research methods such as interviews and focus groups as a means to gain deeper insight into youth financial behaviour as well as their perspectives and experiences of both their financial and overall wellbeing. The study found that it is necessary to expand the narrative of youth financial inclusion beyond an interaction with financial services, products, and interventions. It proposes that an expanded narrative starts with an in-depth understanding of the different layers of youth experiences, as they play out through the personal, relational (social and cultural), and contextual (economic and political). In addition, there is a need to take the dynamicity of different life circumstances and the external environment into account. In this way, a consideration is allowed of the external structures that may, or may not, enable individuals to exercise financial decision-making in pursuit of their overall wellbeing goals. This journey must be walked in order to move away from reductionist wellbeing assessment approaches and resulting in narrowly focused interventions. An approach that centres wellbeing would ultimately take into account the priorities and aspirations of the different stakeholders within an ecosystem, thereby putting in place institutional arrangements that enable solutions that are consistent with broader principles of social and economic justice.